2008
DOI: 10.1677/joe-08-0082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of obestatin in rat and human stomach and plasma, and its lack of acute effect on feeding behavior in rodents

Abstract: Obestatin is a 23-amino acid peptide, initially isolated from rat stomach as an endogenous ligand for the orphan G-proteincoupled receptor. Obestatin is derived from proteolytic cleavage of a 117-amino acid precursor, preproghrelin. Ghrelin increases food intake, body weight, and gastric emptying, whereas obestatin has the opposite effects. In this study, we characterized obestatin in both rat and human stomach, and investigated the peptide's effect on feeding behavior. Using reversed-phase high-performance li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…However, recent studies indicate that obestatin is not the endogenous cognate ligand for GPR39 (Lauwers et al, 2006;Holst et al, 2007;Chartrel et al, 2007), whereas a more recent study demonstrated that obestatin was a metabolic hormone capable of binding to GPR39 and, in turn, of regulating the diverse biological functions of gastrointestinal and adipose tissues (Zhang et al, 2008a). The plasma obestatin concentration did not change after a 450-kcal (Mondal et al, 2008) or even a 1550-kcal (Huda et al, 2008) meal in humans, identifying that obestatin secretion is not influenced by dietary nutrients. The effects of obestatin on food intake 438 remain controversial .…”
Section: Normal Physiology Of Obestatin and Regulation Of Its Expmentioning
confidence: 93%
See 2 more Smart Citations
“…However, recent studies indicate that obestatin is not the endogenous cognate ligand for GPR39 (Lauwers et al, 2006;Holst et al, 2007;Chartrel et al, 2007), whereas a more recent study demonstrated that obestatin was a metabolic hormone capable of binding to GPR39 and, in turn, of regulating the diverse biological functions of gastrointestinal and adipose tissues (Zhang et al, 2008a). The plasma obestatin concentration did not change after a 450-kcal (Mondal et al, 2008) or even a 1550-kcal (Huda et al, 2008) meal in humans, identifying that obestatin secretion is not influenced by dietary nutrients. The effects of obestatin on food intake 438 remain controversial .…”
Section: Normal Physiology Of Obestatin and Regulation Of Its Expmentioning
confidence: 93%
“…Fasting induced the elevation of des-acyl ghrelin, the second ghrelin gene product, in mice (Kirchner et al, 2009), rats (Seoane et al, 2007a), and humans Mondal et al, 2008), whereas feeding suppressed it (Seoane et al, 2007a;Liu et al, 2008;Mondal et al, 2008;Kirchner et al, 2009). Des-acyl ghrelin has been demonstrated to decrease food intake in mice (Asakawa et al, 2005) and rats (Chen et al, 2005a,b) centrally and peripherally in the fasted state.…”
Section: Normal Physiology Of Des-acyl Ghrelin and Regulation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exogenous obestatin inhibited the ghrelin orexigenic effect that was evident in fed mice [20]. On the other hand, many reports have stated that obestatin did not show any effect on food intake in mice or rats [24,32,34,37,[74][75][76]. Obestatin treatment did not modify either daily calorie intake or body-weight gain in highly palatable cafeteria-style diet-fed rats [73].…”
Section: Regulation Of Feeding and Gastrointestinal Motilitymentioning
confidence: 95%
“…Basal obestatin levels in females were higher compared to males [23]. The half-life of obestatin was only 2 min [24]. However, Morash et al recently reported that they did not detect fasting-induced changes in tissue obestatin expression or plasma obestatin level [25].…”
Section: Biological Characteristics Structure and Distributionmentioning
confidence: 96%